2018
DOI: 10.1007/s00107-018-1359-z
|View full text |Cite
|
Sign up to set email alerts
|

Water up-take in fuel pellets studied by Dynamic Vapour Sorption (DVS) analysis and its potential role in self-heating during storage

Abstract: The self-heating of wood fuel pellets is a well-recognised problem causing fire incidents in the storage of the pellets as well as severe intoxication of workers by elevated carbon monoxide and carbon dioxide levels and oxygen depletion. Possible factors contributing to the self-heating are considered to be autoxidation and microbiological activity, while the role and contribution to the temperature rise caused by the heat of condensation from water vapour condensing during fast changes in the relative air hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…It was estimated that the heat from an increase in the moisture content of lignocellulosic material from 5% to 9.5% at a relative humidity of 70% at 20 °C could adiabatically raise the material temperature up to 100 °C, sufficient to induce the carbonization and consequent autoignition . A similar estimation based on measured water uptake of fuel pellets showed that as the relative humidity increased from 40% to 80% at 25 °C, the heat evolution of the first 2 h of water uptake potentially raises the temperature by 45 °C on average and that of the equilibrium water uptake may cause a rise of 87 °C on average . Considering the simultaneous increase of the material temperature during adsorption and thereupon the increase of equilibrium vapor pressure, a theoretical calculation indicated that, however, the water adsorption only possibly raises the temperature to 30–40 °C and just close to 50 °C if the initial material is nearly bone dry .…”
Section: Physical Processes Associated With Watermentioning
confidence: 99%
See 4 more Smart Citations
“…It was estimated that the heat from an increase in the moisture content of lignocellulosic material from 5% to 9.5% at a relative humidity of 70% at 20 °C could adiabatically raise the material temperature up to 100 °C, sufficient to induce the carbonization and consequent autoignition . A similar estimation based on measured water uptake of fuel pellets showed that as the relative humidity increased from 40% to 80% at 25 °C, the heat evolution of the first 2 h of water uptake potentially raises the temperature by 45 °C on average and that of the equilibrium water uptake may cause a rise of 87 °C on average . Considering the simultaneous increase of the material temperature during adsorption and thereupon the increase of equilibrium vapor pressure, a theoretical calculation indicated that, however, the water adsorption only possibly raises the temperature to 30–40 °C and just close to 50 °C if the initial material is nearly bone dry .…”
Section: Physical Processes Associated With Watermentioning
confidence: 99%
“…Heat from physical processes associated with water is released mainly by adsorption and condensation of water vapor from a humid atmosphere, ,, by wetting due to addition of liquid water, or both . It is occasionally observed in the field that a sudden rise in ambient humidity or a rainfall event causes a sharp increase in the pile temperature and even spontaneous combustion. ,, This leads to the suggestion that the heat of wetting may act as a trigger mechanism to increase the pile temperature above a point where other exothermic reactions, especially chemical oxidation, take place and accelerate , and even raise the temperature directly to spontaneous ignition. , However, the reverse processes, that is, water evaporation and desorption, are strongly endothermic. These processes, particularly self-heating driven water vaporization and transport, cause vapor release and heat loss from the pile and therefore have drying and cooling effects .…”
Section: Physical Processes Associated With Watermentioning
confidence: 99%
See 3 more Smart Citations